Atypical progression of multiple myeloma with extensive extramedullary disease. Issue 3 (March 1994) - Jowitt, S N; Jacobs, A; Batman, P A; Sapherson, D A
Abstract : Multiple myeloma is a neoplastic disorder caused by the proliferation of a transformed B lymphoid progenitor cell that gives rise to a clone of immunoglobulin-secreting cells. Other plasma cell tumours include solitary plasmacytoma of bone (SPB) and extramedullary plasmacytomas (EMP). Despite an apparent common origin there exist pathological and clinical differences between these neoplasms and the association between them is not completely understood. A case of IgG multiple myeloma that presented with typical clinical and laboratory features, including a bone marrow infiltrated by well differentiated plasma cells, is reported. The tumour had an unusual evolution, with the development of extensive extramedullary disease while maintaining mature histological features.